Antimicrobial peptide human neutrophil peptide 1 as a potential link between chronic Inflammation and ductal adenocarcinoma of the pancreas - Pausch, Thomas; Adolph, Sarah Anna Julia; Felix, Klaus M.; Bauer, Andrea; Bergmann, Frank; Werner, Jens; Hartwig, Werner (Pancreas, 2018)
Objectives Defensins are antimicrobial peptides playing a role in innate immunity, in epithelial cell regeneration, and in carcinogenesis of inflammation-triggered malignancies. We analyzed this role in pancreatic ductal adenocarcinoma (PDAC) in the context of its association with chronic pancreatitis (CP). - Methods Human tissue of healthy pancreas, CP, and PDAC was screened for defensins by immunohistochemistry. Defensin α 1 (human neutrophil peptide 1 [HNP-1]) expression was validated using mass spectrometry and microarray analysis. Human neutrophil peptide 1 expression and influences of proinflammatory cytokines (tumor necrosis factor α, interleukin 1β, and interferon γ) were studied in human pancreatic cancer cells (Colo 357, T3M4, PANC-1) and normal human pancreatic duct epithelial cells (HPDE). - Results Accumulation of HNP-1 in malignant pancreatic ductal epithelia was seen. Spectrometry showed increased expression of HNP-1 in CP and even more in PDAC. At RNA level, no significant regulation was found. In cancer cells, HNP-1 expression was significantly higher than in HPDE. Proinflammatory cytokines significantly led to increased HNP-1 levels in culture supernatants and decreased levels in lysates of cancer cells. In HPDE cytokines significantly decreased HNP-1 levels. - Conclusions Inflammatory regulation of HNP-1 in PDAC tissue and cells indicates that HNP-1 may be a link between chronic inflammation and malignant transformation in the pancreas.